Occurrence and ecological risk assessment of antibiotics in manure and the surrounding soil from typical chicken farms in Hangzhou, China - Zha, Yan; Li, Qinghai; Liu, Hang; Ge, Ying; Wei, Yinghui; Wang, Huanhuan; Zhang, Lei; Fan, Jinghui; Chen, Yi; Zhang, Chengxian; Zhou, Tiefeng; Zhang, Weiwu (Frontiers in Environmental Science, 2023)
The widespread use of antibiotics in animal and human medication has raised global concerns over environmental contamination caused by antibiotic residues. This research investigated the occurrence of 12 kinds of antibiotics belonging to three groups, sulfonamides (SAs), tetracyclines (TCs), and fluoroquinolones (FQs), in chicken manure and the surrounding soil from different chicken farms in Hangzhou, South China, and evaluated their ecological risk. The results indicated that: the total concentration of FQs was much higher than those of SAs and TCs in chicken manures and the soil samples. The mean concentration of FQs (39.17 μg•kg -1 ), TCs (34.37 μg•kg -1 ), and SAs (20.24 μg•kg -1 ) in chicken manure were significantly higher than those in the soil samples. Ciprofloxacin (CIP) was the main antibiotics detected in manure (19.42 μg•kg -1 ) and the soils samples (near soil: 18.42 μg•kg -1 , far soil: 10.29 μg•kg -1 ), followed by enrofloxacin (ENR), tetracycline (TC), and ofloxacin (OFL). The redundancy analysis (RDA) showed that moisture content (MS), total organic carbon (TOC) and total nitrogen (TN) had a greater influence on the antibiotic concentration in the soil samples. Basis on the calculated risk quotient (RQs) values, the risk assessment indicated Sulfamerazine (SD) and Sulfamethoxazole (SMX) in soil posed a high risk, while trimethoprim (TMP), TC, CIP, and OFL in soils posed a medium or low risk. This research provides control and Running Title 2 environmental monitoring data about chicken farms and scientific information that can be used to alleviate antibiotics pollution.